Utility of Student-Run Free Clinics for Underserved Individuals During COVID-19 Michigan Shelter-in-Place Order - Sara Saymuah Stone; Hailey Heil; Janki Vaghasia; Marla Rojas Thaureaux; Victoria Badia; Paige Baal (Journal of Student-Run Clinics, 2021)
Student-run free clinics (SRFCs) serve individuals who would not otherwise have access to healthcare. Cass Clinic, a SRFC affiliated with Wayne State University School of Medicine in Detroit, Michigan, serves a predominantly underprivileged population by providing free physical examinations, laboratory testing, medications, and resources such as hand sanitizer and surgical masks. Despite the Coronavirus Disease 2019 (COVID-19) pandemic and Michigan Governor Gretchen Whitmer’s shelter-in-place order from March 24, 2020 through June 12, 2020, Cass Clinic remained open to serve Detroit patients. To assess the utility of SRFCs in meeting patient needs during the Michigan shelter-in-place order, quality assessment surveys were conducted. Patients reported seeking care at Cass Clinic due to lack of resource availability at supply stores and lack of healthcare access at other clinics. All participants reported receiving medication refills for chronic conditions due to a general patient concern of inability to obtain medications through other healthcare services. Surveys demonstrated Cass Clinic provides essential services to underserved individuals by adequately managing chronic conditions such as hypertension and type two diabetes mellitus. Cass Clinic, and SRFCs in general, serve a vital role throughout the Michigan shelter-in-place order by continuing healthcare management for patients who are at a disproportionate risk of adverse health outcomes due to COVID-19.